Penentuan Kadar Total Flavonoid Kunyit Putih (Curcuma zedoria Rosc.) dengan Variasi Jenis Pelarut - Sitti Aminah; Evayana Evayana (Media Eksakta, 2022)
Determination of Total Levels of White Turmeric Flavonoids (Curcuma zedoria Rosc.) with Variation of Solvent Types. White turmeric (Curcuma zedoria Rosc.) is a herbal plant that has many health benefits in healing several diseases. It can grow wild in the open with moist soil. The purpose of this study was to determine the total levels of white turmeric flavonoids with various types of solvents. The solvents used in were water and ethanol. The quantitative test of flavonoids in the White Turmeric extract used a quercetin standard solution curve. The samples were analyzed by UV-Vis spectrophotometry at a maximum wavelength of 435 nm. The average yield obtained in the water extract was 0,073% and 0,102% in the ethanol extract.   Keywords: Flavonoids, White Turmeric, UV-Vis Spectrophotometry